2021
DOI: 10.1038/s41598-021-91539-y
|View full text |Cite
|
Sign up to set email alerts
|

In-situ remediation of nitrogen and phosphorus of beverage industry by potential strains Bacillus sp. (BK1) and Aspergillus sp. (BK2)

Abstract: The bioremediation of beverage (treated and untreated) effluent was investigated in the current study by using the potential strains of Bacillus sp. (BK1) and Aspergillus sp. (BK2). Effluent was collected from the beverage industry (initial concentration of nitrogen were 3200 ± 0.5 mg/L and 4400 ± 0.6 mg/L whereas phosphorus were 4400 ± 2 mg/L and 2600 ± 1 mg/L in treated and untreated effluent correspondingly). Further, the BK1 and BK2 exhibited high removal competence after 1 week of incubation; BK1 removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…In this present study we found 27 indigene bacteria which were divided into eight genera, Pseudomonas, Bacillus, Neisseria, Micrococcus, Staphylococcus, Proteus, Acinetobacter, and Escherichia. These findings are in line with previous study that isolated the bacteria from different source of waste [11,12]. In a previous study, three genera, Aeromonas, Pseudomonas and Bacillus, were isolated from the landfill leachate [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this present study we found 27 indigene bacteria which were divided into eight genera, Pseudomonas, Bacillus, Neisseria, Micrococcus, Staphylococcus, Proteus, Acinetobacter, and Escherichia. These findings are in line with previous study that isolated the bacteria from different source of waste [11,12]. In a previous study, three genera, Aeromonas, Pseudomonas and Bacillus, were isolated from the landfill leachate [13].…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, three genera, Aeromonas, Pseudomonas and Bacillus, were isolated from the landfill leachate [13]. Previous studies have even explored the ability of the isolated bacteria in bioremediation, including biodegrading microplastics [11][12][13].…”
Section: Discussionmentioning
confidence: 99%